Resurgence of influenza and enterovirus infections in Taiwan post-COVID-19: A nationwide surveillance study - Nan-Chang Chiu; Daniel Tsung-Ning Huang; Shun-Long Weng; Hsin Chi; Yu-Lin Tai; Ya-Ning Huang; Hsiang Huang; Wei-Te Lei; Lung Chang; Chien-Yu Lin (Elsevier, 2024)
Background: The global impact of COVID-19 has prompted profound shifts in public health policies. The epidemiology of respiratory infectious disease may change in the post-covid era. This study investigates the repercussions of these policies on respiratory infectious diseases, specifically the resurgence of severe influenza and enterovirus infections in the post-COVID-19 era. Methods: Examining the period from January 2020 to December 2023, our nationwide study analyzes data from the Taiwan Centers for Disease Control and Our World in Data. Two distinct phases, containing (Week 1, 2020, to Week 43, 2022) and coexisting (Week 44, 2022, to Week 50, 2023), are scrutinized, emphasizing policy changes and their potential impact on epidemiology. Results: Epidemiological trends reveal a decline in COVID-19 and all-cause pneumonia during the co-existing period but a notable rise in severe influenza and enterovirus infections. Interrupted time series analysis confirms the surge in severe influenza and enterovirus cases post-restriction ease. Conclusion: The post-COVID-19 era introduces challenges with the resurgence of traditional respiratory diseases, necessitating continuous surveillance, timely non-pharmaceutical interventions, and vaccination as crucial strategies. Vigilance and targeted measures by policymakers and healthcare providers are imperative to navigate the evolving landscape of respiratory infectious diseases in the aftermath of the pandemic.